Prolonged Sitting, Its Combination With Physical Inactivity and Incidence of Lung Cancer: Prospective Data From the HUNT Study - Jiang, Lin; Sun, Yi-Qian; Brumpton, Ben Michael; Langhammer, Arnulf; Chen, Yue; Nilsen, Tom I. L.; Mai, Xiao-Mei (Frontiers in Oncology, 2019)
Background: Prolonged sitting as a major sedentary behavior potentially contributes to illness, but its relation with lung cancer risk is unclear. Prolonged sitting can be presented in physically active or inactive individuals. Those who are extendedly seated and also physically inactive may represent the most sedentary people. We therefore aimed to prospectively examine if total sitting time daily itself or in combination with physical activity is associated with lung cancer incidence overall and histologic types. Methods: We included 45,810 cancer-free adults who participated in the second survey of HUNT Study in Norway (1995-97), with a median follow-up of 18.3 years. Total sitting time daily and physical activity were self-reported at baseline. Lung cancer cases were ascertained from the Cancer Registry of Norway. Cox regression was used to estimate hazard ratios (HRs) with 95% confidence intervals (CIs). Results: In total, 549 participants developed lung cancer during the follow-up. Total sitting time daily was not associated with the incidence of lung cancer overall and histologic subtypes. Compared with participants sitting <8 hours daily and being physically active, those sitting ≥8 hours daily (prolonged sitting) and being physically inactive had an increased incidence of lung cancer (overall: adjusted HR = 1.44, 95% CI: 1.07-1.94; small cell lung cancer: adjusted HR = 2.58, 95% CI: 1.23-5.41). Prolonged sitting only or physical inactivity only was not associated with the incidence of lung cancer. Conclusions: Our study suggested that prolonged sitting was not independently associated with lung cancer incidence. The combination of prolonged sitting and physical inactivity might increase the risk of lung cancer. However, residual confounding by smoking cannot be excluded completely even though smoking was adjusted for with detailed information.